The Winnipeg Strike Trials - Greening, E. (Relations industrielles / Industrial Relations, 1965)
The author describes the events which brought about and accompanied the Winnipeg general strike in Spring 1919, where many individual were arrested. The main interest of Mr. Greening bears upon the trials which followed. Attention is drawn on the following issues: Under what counts the persons involved in the strike were indicted by the Canadian Government? What was the content of the agreements evoked by both parties at the trial? What was the general social context in which those events took place? The interest of the author is to give a tentative answer to those questions.